Acknowledgment of research accomplishment - Angastiniotis, Nicos (My University, 2026)
Acknowledgment of research accomplishment by the Handbook of Nanophase Materials, Avery N. Goldstein, The Dow Chemical Company, Midland, Michigan, ISBN 0-8247-9469-9, Marcel Dekker, Inc., 1997
Keywords: Arts and entertainment